Construction and characterization of a contagious ecthyma virus double-gene deletion strain and evaluation of its potential as a live-attenuated vaccine in goat - Zhu, Zhen; Qu, Guanggang; Du, Jige; Wang, Changjiang; Chen, Yong; Shen, Zhanning; Zhou, Zhiyu; Yin, Chunsheng; Chen, Xiaoyun (Frontiers in Immunology, 2022)
Contagious ecthyma is a highly contagious viral disease with zoonotic significance caused by ORFV that affects domestic, ruminants and humans. Live attenuated virus and attenuated tissue culture vaccines are widely used in the fight against ORFV, however, the conventional attenuated vaccine strains have many drawbacks. The aim of this project was to construct a promising contagious ecthyma vaccine strain with safety, high protection efficacy and accessibility by genetic manipulation to against the disease. Using the natural attenuated ORFV-GS14 strain as the parental virus, recombinant virus, rGS14-ΔCBP-ΔGIF, with double deletions in the genes encoding the chemokine binding protein (CBP) and granulocyte/macrophage colony-stimulating factor inhibitory factor (GIF) was generated and characterized in vitro and in vivo. Results showed that the growth kinetics curve of rGS14-ΔCBP-ΔGIF and parental virus was consistent, both reaching plateau phase at 48 h post infection, which indicated that the double deletion of cbp and gif genes had little impact on the replication properties of the recombinant virus in primary goat testis (PGT) cell cultures compared with the parental virus. The safety of the double gene-deleted virus was evaluated in lambs. The lambs were monitored for 21 days post infection of the recombinant virus and no ORFV associated symptoms were observed in 21 days post-infection except for slight fever and anorexia in 5 days post-infection, and all lambs inoculated with either recombinant virus or PBS exhibited no clinical signs. To assess the protection efficacy of the rGS14-ΔCBP-ΔGIF, groups of four lambs each were inoculated with rGS14-ΔCBP-ΔGIF, rGS14-ΔCBP, rGS14-ΔGIF or PBS and challenged by a wild type virulent ORFV strain at 21-day post-inoculation. During 14 days post-challenging, lambs inoculated with rGS14-ΔCBP-ΔGIF all remained healthy with unimmunized group all infected, while the single gene-deleted viruses only protected 40% to 50% animals. These results indicated that the double gene-deleted recombinant virus could provide complete protection against virulent ORFV challenging. In conclusion, the double gene-deleted recombinant virus strain, rGS14-ΔCBP-ΔGIF, would be a promising candidate vaccine strains with safety, high protection efficacy and availability.